2018
DOI: 10.7150/thno.24056
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-suppressing miR-141 gene complex-loaded tissue-adhesive glue for the locoregional treatment of hepatocellular carcinoma

Abstract: microRNAs (miRNAs) regulate gene expression post-transcriptionally and have been extensively tested as therapeutic molecules against several human diseases. In vivo delivery of miRNAs needs to satisfy the following conditions: safety, efficiency, and long-term therapeutic effectiveness. To satisfy these conditions, we developed a tissue-adhesive nucleotide-polymer complex (NPX-glue) for in vivo delivery of miRNAs to treat hepatocellular carcinoma (HCC).Methods: Polyallylamine (PAA), a cationic polymer, was mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…miRNA deregulation and dysfunction play a significant role in human cancer pathogenesis 4-6. Mature miRNAs, a class of ~22 nucleotide-long RNA molecules, are cleaved from long hairpin miRNA precursors by the cytoplasmic RNase III, Dicer.…”
Section: Introductionmentioning
confidence: 99%
“…miRNA deregulation and dysfunction play a significant role in human cancer pathogenesis 4-6. Mature miRNAs, a class of ~22 nucleotide-long RNA molecules, are cleaved from long hairpin miRNA precursors by the cytoplasmic RNase III, Dicer.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, TM4SF1 was shown to increase E-cadherin expression through the AKT signaling pathway in pancreatic and colorectal cancers (Zheng B. et al, 2015;Xu D. et al, 2020). Kim et al (2018) demonstrated that miR-141 expression was related to TM4SF1 in pancreatic cancer, and upregulating miR-141, which decreased TM4SF1, reduced E-cadherin and VEGF-A to accelerate EMT in pancreatic cancer cells.…”
Section: Tm4sf1 Promotes Emtmentioning
confidence: 95%
“…Therefore, many vectors have been used to improve the stability of oligonucleotides. However, these drugs are di cult to achieve targeted drug delivery (18). We believe that miR-141-5p and si-hsa_circ_0063526 have the best therapeutic effect as an intraperitoneal injection (44).…”
Section: Discussionmentioning
confidence: 99%